Exploring the influence of COVID-19 on the utilisation of the Employee assistance programme within a private medical laboratory in South Africa - Mavuso, Grisselda Sithembile (University of the Witwatersrand, Johannesburg, 2023)
Employee assistance programmes (EAPs) are programmes designed to support employees to handle challenges that may affect their work performance. The programmes assist them to adopt behaviors that promote health, improve quality of life, support their personal growth and effectiveness, and ultimately contribute to the organization's bottom line. Despite the availability of EAP services, the prevalence of mental health disorders remains high both in South Africa, and the rest of the world. The COVID-19 pandemic presented a novel form of stressor in many lives globally and it negatively impacted employees worldwide. Health care workers, including medical laboratory workers, were hit the most by the effects of COVID-19 as they faced infected patients or infected patient samples on a daily basis. The aim of the study was to assess the impact of COVID-19 on the EAP usage in one of the largest private medical laboratories in South Africa. The study assessed if there were any notable changes in the use of the programme in year 2020 compared to the pre- COVID-19 period years 2018 to 2022. The study also aimed to understand the perceptions of the employees towards the programme and to find out if there are any benefits that the EAP offers to them. Many of the study’s interviewed respondents reported that COVID-19 presented immense psychological pressure in their lives. However, despite the severe negative impact of COVID-19, fewer respondents utilised the EAP in that COVID-19 period. Discrepant findings were however noted between the interviews and the secondary EAP data. Secondary data showed that there was an increase in the EAP usage rates between year 2020 - 2021, up to 20.4% from 15.37 % in year 2019. The respondents who have used the EAP reported that they derived great benefits from it
A research report submitted in partial fulfillment of the requirements for the degree of Master of Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: employee wellbeing; Health care workers; Burn-out; Essential workers; Mental health; UCTD; SDG-8: Decent work and economic growth